Transforming Islamic Learning into Digital Edutainment: YouTube Education for Elementary School-Aged Children - Rachman, Rio Febriannur; Rodiyah, Nuning (Bidayatuna Jurnal Pendidikan Guru Mandrasah Ibtidaiyah, 2026)
The rapid development of digital media has transformed the landscape of Islamic education, particularly for elementary school-aged children. This study aims to examine how YouTube channels, specifically Nussa Official and Riko the Series, function as alternative media for delivering basic Islamic education. Using a qualitative content analysis approach based on Krippendorff and interpreted through Miguel Sabido’s entertainment-education framework, this research analyzes the structure, narratives, and thematic patterns within the content of both channels. The findings reveal that these animated videos integrate educational and entertainment elements to convey religious values in an engaging and accessible manner. The narratives predominantly employ transitional characters, allowing children to learn through processes of transformation from not knowing to knowing, and from inappropriate to appropriate behavior, rather than through rigid moral dichotomies. Furthermore, the content consistently embeds core Islamic teachings (aqidah, syariat, and akhlak) within everyday contexts, making them relatable and practical for young audiences. The open nature of digital platforms, including interactive features and cross-platform integration, also contributes to the democratization of education, enabling broader participation in the dissemination and reinforcement of educational values. This study concludes that YouTube serves not only as a medium of entertainment but also as an effective space for informal Islamic education that aligns with contemporary learning needs and supports the realization of quality education in the digital era.